DEVELOPING INTERACTIVE MULTIMEDIA FOR READING AT TEST OF STANDARD ENGLISH (PENGEMBANGAN MULTIMEDIA INTERAKTIF READING PADA TEST OF STANDARD ENGLISH) - Fithriyah Nurul Hidayati (Leksema: Jurnal Bahasa dan Sastra, 2017)
This research aims to develop interactive multimedia (web-based) to improve students’ Reading score of Test of Standard English (TOSE). This research was conducted at the FITK IAIN Surakarta on Reading class with 30 students. The data for the research were gathered by questionnaires, interviews, and observations. The data analysis used qualitative descriptive method. This study used research and development (R & D) assigning TOSE Students and the lecturer in the program. The stages of R & D devised by Bord & Gall (2003) were implemented in the study, covering exploration and development of prototype. Exploration stages commenced from needs analysis and development of prototype. The development of prototype began with devising reading materials in interactive multimedia. The prototype was evaluated based upon expert judgment. The findings show that the interactive multimedia provide chat room, hyperlinks, TOSE exercises, and interesting materials.